Anatomy of Subcortical Structures Predicts Age-Related Differences in Skill Acquisition. (1st December 2016) - Chalavi, Sima; Adab, Hamed Zivari; Pauwels, Lisa; Beets, Iseult A M; van Ruitenbeek, Peter; Boisgontier, Matthieu P; Monteiro, Thiago Santos; Maes, Celine; Sunaert, Stefan; Swinnen, Stephan P
Abstract: Skill acquisition capabilities vary substantially from one individual to another. Volumetric brain studies have demonstrated that global volume of several subcortical structures predicts variations in learning outcome in young adults (YA) and older adults (OA). In this study, for the first time, we utilized shape analysis, which offers a more sensitive detection of subregional brain anatomical deformations, to investigate whether subregional anatomy of subcortical structures is associated with training-induced performance improvement on a bimanual task in YA and OA, and whether this association is age-dependent. Compared with YA, OA showed poorer performance, greater performance improvement, and smaller global volume and compressed subregional shape in subcortical structures. In OA, global volume of the right nucleus accumbens and subregional shape of the right thalamus, caudate, putamen and nucleus accumbens were positively correlated with acquisition of difficult (non-preferred) but not easy (preferred) task conditions. In YA, global volume and subregional shape of the right hippocampus were negatively correlated with performance improvement in both the easy and difficult conditions. We argue that pre-existing neuroanatomical measures of subcortical structures involved in motor learning differentially predict skill acquisition potential in YA and OA.